The Nexus Between Data-Driven Decision-Making, Market Responsiveness, and Strategic Alliances in Boosting Business Growth of Start-Up Companies - Lisbet, Zeanette T; Al Faroqi, Fachmi; Evelyna, Feby; Prihadi, Donny Juliandri (International Journal of Business, Law, and Education, 2024)
This study explores the nexus between data-driven decision-making, market responsiveness, and strategic alliances in fostering business growth among start-up companies. Utilizing a quantitative research design, data were collected through surveys distributed to start-up firms, resulting in a sample that highlights the relationships among key constructs. The analysis, conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM), reveals that data-driven decision-making significantly influences business growth, with market responsiveness acting as a mediator and strategic alliances serving as a moderator in this relationship. The findings underscore the importance of leveraging data analytics to enhance responsiveness to market dynamics and establishing strategic partnerships to optimize growth outcomes. This research provides actionable insights for start-ups aiming to navigate competitive environments and drive sustainable growth.